Metallic Nanowire Coupled CsPbBr3 Quantum Dots Plasmonic Nanolaser. (28th April 2021) - Xing, Di; Lin, Cheng‐Chieh; Won, Phillip; Xiang, Rong; Chen, Tzu‐Pei; Kamal, A. Syazwan A.; Lee, Yang‐Chun; Ho, Ya‐Lun; Maruyama, Shigeo; Ko, Seung Hwan; Chen, Chun‐Wei; Delaunay, Jean‐Jacques
Abstract: Plasmonic nanolasers provide a valuable opportunity for expanding sub‐wavelength applications. Due to the potential of on‐chip integration, semiconductor nanowire (NW)‐based plasmonic nanolasers that support the waveguide mode attract a high level of interest. To date, perovskite quantum dots (QDs) based plasmonic lasers, especially nanolasers that support plasmonic‐waveguide mode, are still a challenge and remain unexplored. Here, metallic NW coupled CsPbBr3 QDs plasmonic‐waveguide lasers are reported. By embedding Ag NWs in QDs film, an evolution from amplified spontaneous emission with a full width at half maximum (FWHM) of 6.6 nm to localized surface plasmon resonance (LSPR) supported random lasing is observed. When the pump light is focused on a single Ag NW, a QD‐NW coupled plasmonic‐waveguide laser with a much narrower emission peak (FWHM = 0.4 nm) is realized on a single Ag NW with the uniform polyvinylpyrrolidone layer. The QDs serve as the gain medium while the Ag NW serves as a resonant cavity and propagating plasmonic lasing modes. Furthermore, by pumping two Ag NWs with different directions, a dual‐wavelength lasing switch is realized. The demonstration of metallic NW coupled QDs plasmonic nanolaser would provide an alternative approach for ultrasmall light sources as well as fundamental studies of light matter interactions. Abstract : Quantum dot (QD)‐nanowire (NW) based plasmonic lasers are demonstrated by embedding Ag NWs in a CsPbBr3 QDs film. The evolution from amplified spontaneous emission to a localized surface plasmon resonance‐supported random lasing is observed. Further, a plasmonic‐waveguide laser is also achieved with a narrow bandwidth of 0.4 nm. By using the QD‐NW plasmonic‐waveguide lasers, a dual‐wavelength nanolaser switch is realized.